Providing Privacy in Profile Based Personalized Web Search - Sajjan, Rajani S; Veer, Suvarna A (International Journal of Computer Sciences and Engineering, 2019)
Web search engines (e.g. Google, Yahoo, Microsoft Live Search, Bing, etc.) are mostly used to search certain information from a large amount of data in a very few amount of time. Aforementioned engines are built for all kind of people and not for any particular client that is, it gives generalized result for input query and not user specific result, to address this problem personalized web search is best way to increase the accuracy of web search in terms of giving user specific results. However, effective personalized web search requires gathering and aggregating user information (e.g. user name, contact no, etc), which often raises serious concerns of privacy infringement for many users. In fact, these privacy concerns have become one of the major reasons for deploying personalized web search applications and how to do privacy-preserving personalization is a great challenge. In this proposed system, we propose and try to resist adversaries with broader background knowledge, such as richer relationship among topics. Richer relationship means we generalize the user profile results by using the background knowledge which is going to store in history. Through this we are able to hide the user search results. By using this new mechanism, we can achieve the better privacy and improve better search quality results.